2004
DOI: 10.1021/la035502f
|View full text |Cite
|
Sign up to set email alerts
|

Quartz Crystal Microbalance (QCM) in High-Pressure Carbon Dioxide (CO2):  Experimental Aspects of QCM Theory and CO2 Adsorption

Abstract: The quartz crystal microbalance (QCM) technique has been developed into a powerful tool for the study of solid-fluid interfaces. This study focuses on the applications of QCM in high-pressure carbon dioxide (CO2) systems. Frequency responses of six QCM crystals with different electrode materials (silver or gold) and roughness values were determined in helium, nitrogen, and carbon dioxide at 35-40 degrees C and at elevated pressures up to 3200 psi. The goal is to experimentally examine the applicability of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
52
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 29 publications
0
52
0
Order By: Relevance
“…Wu et al 29 have shown that these additional effects are much smaller than the influence of viscosity when resonators with polished surfaces are immersed in fluids chemically inert. Besides the influence of viscous damping, the adsorption and the slipping of molecules from the gas phase, the roughness of the electrode surface of the quartz resonator may lead to variations ⌬f sl , ⌬f R in the resonance frequency of the crystal.…”
Section: Methodsmentioning
confidence: 99%
“…Wu et al 29 have shown that these additional effects are much smaller than the influence of viscosity when resonators with polished surfaces are immersed in fluids chemically inert. Besides the influence of viscous damping, the adsorption and the slipping of molecules from the gas phase, the roughness of the electrode surface of the quartz resonator may lead to variations ⌬f sl , ⌬f R in the resonance frequency of the crystal.…”
Section: Methodsmentioning
confidence: 99%
“…This behavior was reproducible in response to the pressure. A plateau in the frequency-shift curve from the reference QCM was observed before and interpreted as a pressure-induced effect [21]. However, in good contrast with the reference QCM, a significant frequency drop in the SWCNT-loaded QCM is ascribed to the hydrogen adsorption.…”
Section: Methodsmentioning
confidence: 78%
“…The QCM technique is particularly well adapted for measurements of uptake rates of vapor-phase lubricants, providing a sensitive, real-time means for monitoring mass uptake [10], and tribological properties of the adsorbed film and/or its reaction products [7,8,11]. QCM is also an attractive technique for comparative studies of macroscopic and microscopic phenomena, owing to the high-sliding speeds (up to 2 m/s) and shear rates at which the data are recorded [12].…”
Section: Friction Measurements By Means Of Qcmmentioning
confidence: 99%